Beta-glucosidase and esterase activity from Oenococcus oeni: Screening and evaluation during malolactic fermentation in harsh conditions. (March 2018) - Fia, Giovanna; Millarini, Valentina; Granchi, Lisa; Bucalossi, Ginevra; Guerrini, Simona; Zanoni, Bruno; Rosi, Iolanda
Abstract: The β-glucosidase and esterase activities of 31 O. oeni strains were evaluated by fluorimetric methods. The level and distribution among intact cells and supernatant of both β-glucosidase and esterase activity in MRS broth were strongly strain-dependent. In the wine, hydrolytic activities were detected only in the intact cells and their level was related to the cell growth and malolactic activity. Increasing concentration of ethanol (from 12 to 15 (% v/v)) and molecular SO2 (from 0.2 to 0.6 mg L −1 ) led to a slowdown of bacterial growth and malolactic fermentation (MLF). An inhibitory effect of the lowest doses of molecular sulphur dioxide on both β-glucosidase and esterase activity was highlighted. A synergistic effect among SO2 and ethanol on hydrolytic activities was observed during MLF. Only one strain was able to complete MLF and to produce both hydrolytic activities also in the harshest conditions. Highlights: β-glucosidase and esterase activity from O. oeni in harsh wine was studied. Both hydrolytic activities depend on the cell growth and malolactic activity. Small doses of molecular SO2 inhibit both β-glucosidase and esterase activity. A synergistic effect between SO2 and ethanol on hydrolytic activities was observed. Few strains complete MLF and produce both hydrolytic activities in the harshest wine.